OPPORTUNITIES AND EFFECTIVE TOOLS OF THE MODERN AUDIENCE IN TEACHING INFORMATION TECHNOLOGIES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
Objective. In this article, conclusions and suggestions formed as a result of deploying innovasion technologies which are considered to be essential to use in every processes of education will be stated. Some factors stimulating the educational activity of students are analyzed, and examples are given. Questions and situations used in problem-based learning are applicable to the learning process of information technology. Results. According to the results, the each lesson, topic, subject has its own technology. Pedagogical technology in the learning process is a holistic process in a specific sequence, which is a goal-oriented, well-designed and guaranteed pedagogical result based on the needs of the student. The realization of the pedagogical goal and the achievement of a guaranteed result depends on the joint activity of the teacher and the student, the goal they set, the chosen content, style, form, means, ie technology. Conclusion. Based on our personal experience, it has been found that the following factors, which stimulate students' cognitive activity and which many do not pay much attention to, are more effective in the formation of basic knowledge. Keywords: cognitive activity, systematic approach, pedagogical technology, goal orientation, pedagogical process, problem situation, logical observation, creative activity.